THE PLACE AND ROLE OF TECHNICAL TRAINING IN THE ORGANIZATION OF TECHNICAL SUPPORT IN THE TROOPS (American Journal of Interdisciplinary Research and Development, 2026)
This article describes the concept of technical support, the main tasks of technical support, the concept of technical training, its tasks, goals and procedures of the organization, the place and role of technical training in the organization of technical support in modern conditions.